Pengembangan Media Pembelajaran Fisika berbantuan 3D Application Scratch pada Topik Gerak Parabola - Nurita Annisa; Riki Perdana (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
The fundamental problem that is often experienced in learning physics in the classroom lies in the limited use of learning media in conveying complex physics concepts. Therefore, the main objective of this research is to develop Scratch-based learning media on parabolic motion material. This research adopts the 4D approach which involves the stages of Define, Design, Development, and Disseminate. The method includes literature study, Scratch media development, and feasibility test. The results of the study show the average feasibility test of each aspect, and the feasibility test results show an average score of 3.45 which is included in the very feasible category and indicates that this media can be used in physics learning. The novelty of this article lies in the innovative integration between theory and practical application of Scratch which makes it a valuable contribution to the development of technology-based physics education.